Diskurs - interdisziplinär: Zugänge, Gegenstände, Perspektiven - Kämper, Heidrun; Warnke, Ingo H. (Diskursmuster, 2015)
"What happens when philosophers and sociologists, historians, literary scholars, and linguists try to engage in discourse? The essays in this volume examine this question and describe the structure of discourses as instances of meaning-production based on a common basic understanding of "discourse" from a theoretical, methodological, and empirical perspective"--
Literaturangaben
Vorl. Bd. enth. Vorträge, die auf der ersten (7. und 8. November 2011) und zweiten Tagung (27. bis 29. November 2012) des Netzwerks "Diskurs - interdisziplinär" gehalten wurden. [Tagungsort Mannheim erm.]
Keywords: Konferenzschrift -- 2011 -- Mannheim; Kritische Diskursanalyse; Geschichtsschreibung; Diskursanalyse; Linguistik